THE EFFECT OF HEURISTICS, PROSPECTS, AND HERDING BEHAVIOR ON INVESTMENT DECISIONS-MAKING - Wirayana, I Made Adhi; Dwija Putri, I Gusti Ayu Made Asri; Sari, Maria M. Ratna; Agung Suaryana, I Gusti Ngurah (International Journal of Psychosocial Rehabilitation, 2020)
Psychological factors drive the irrational behavior of the investor’s decision-making. This study aims to obtain empirical evidence on the effect of heuristics, prospects, and herding behavior on investment decision-making. The sampling technique used was a convenience sampling technique. This study used primary data obtained using survey methods conducted by giving questionnaires to the younger generation in Denpasar City, Bali Province, Indonesia, who invests stock in the Indonesian Capital Market. Data analysis techniques using the structural equation (SEM) approach using Partial Least Square (PLS) software. The results show that heuristic and herding behaviors influence investment decision making, whereas prospect behavior does not affect young generation investment- decision making.